1961
DOI: 10.1111/j.1365-2389.1961.tb00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Pollen Analysis

Abstract: SummaryAcidic soils (pH below 5.5) may contain a great deal of pollen through the profile, and the floristic composition of this pollen may vary greatly in samples from successively greater depths.Various attempts have been made in the past to interpret pollen diagrams from soils, but they have usually broken down through the application of methods of interpretation which are only applicable to properly stratified materials such as peats or lake sediments. Once it is appreciated that downwash of pollen through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
1

Year Published

1974
1974
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 3 publications
0
22
1
1
Order By: Relevance
“…High percentages of indeterminant palynomorphs, usually >50%, and low pollen concentration are signs of differential preservation, and general loss of pollen grains is due to oxidation, biological agents such as bacteria and phycomycete fungi, and high pH (Bryant et al 1994, Bryant andHolloway 1996). Those processes including the vertical transport of palynomorphs through sediments via water (downwash) or by animal activity (bioturbation) are comparable to processes observed in terrestrial soils (Dimbleby 1961;Davidson et al 1999;Gavin and Brubaker 1999). Consequently, the pollen concentration in archaeological contexts, especially in dry soils in arid regions, is often too low to achieve a precise portrait of the vegetation, the record is usually greatly influenced by anthropogenic disturbances and alteration of palynomorphs has often led to overrepresentation of more resistant pollen types (Fish 1989, see references in Lebreton et al 2010).…”
Section: Objectivesmentioning
confidence: 87%
“…High percentages of indeterminant palynomorphs, usually >50%, and low pollen concentration are signs of differential preservation, and general loss of pollen grains is due to oxidation, biological agents such as bacteria and phycomycete fungi, and high pH (Bryant et al 1994, Bryant andHolloway 1996). Those processes including the vertical transport of palynomorphs through sediments via water (downwash) or by animal activity (bioturbation) are comparable to processes observed in terrestrial soils (Dimbleby 1961;Davidson et al 1999;Gavin and Brubaker 1999). Consequently, the pollen concentration in archaeological contexts, especially in dry soils in arid regions, is often too low to achieve a precise portrait of the vegetation, the record is usually greatly influenced by anthropogenic disturbances and alteration of palynomorphs has often led to overrepresentation of more resistant pollen types (Fish 1989, see references in Lebreton et al 2010).…”
Section: Objectivesmentioning
confidence: 87%
“…As mentioned by Dimbleby (1957), an alkaline environment is not ideal for pollen preservation. The pollen numbers can be very low in sediments with a pH greater than 5.5 (Dimbleby, 1961). In other mangroves, a high pH value of the sediments leads to a poor fossilization potential of the mangrove pollen (Grindrod, 1988;Wang and Chappell, 2001), while in terrestrial forests, a decrease in pollen concentrations is associated with an increase in soil pH.…”
Section: Palynomorph Degradationmentioning
confidence: 97%
“…Oxidation, the pH value of soil, aridity, organic matter content and microorganism are the external factors that influence pollen preservation. Dimbleby (1957;1961) thought that the soil pH value is the most important factor that determines the pollen preservation. He found that when pH is higher than 5.5, the pollen concentrations decrease abruptly.…”
Section: Low Representation Of Betula-populus Pollenmentioning
confidence: 99%